Pediatric Inflammatory Bowel Disease Associated With Celiac Disease: A Retrospective Study in a Tertiary Care Hospital in Saudi Arabia - Mamdouh Qadi Medical Student; Mohammed Hasosah MD; Anas Alamoudi Medical Student; Abdullah AlMansour Medical Student; Mohammed Alghamdi Medical Student; Faisal Alzahrani Medical Student; Sultan Alzahrani Medical Student; Bader Khawaji PhD (SAGE Publishing, 2021)
Background. Inflammatory bowel disease (IBD), which includes ulcerative colitis (UC) and Crohn's disease (CD), is a chronic relapsing disease indicated by inflammation of the gastrointestinal tract. Celiac disease (CeD) is a chronic autoimmune disease of the small bowel. The prevalence of CeD in IBD patients is unknown. Some studies have described the coexistence of the 2 diseases in the same patient. This study aimed to investigate the prevalence of CeD in Saudi Arabian children with IBD. Methods. We used a retrospective study design because data can be collected immediately and is easier to analyze afterward. The study was conducted on IBD patients in the Pediatric Gastroenterology Department at National Guard Hospital, Jeddah, Saudi Arabia. We enrolled Saudi patients aged between 1 and 18 years who had been diagnosed with IBD and CeD based on positive biochemical serology and histology from January 2011 to January 2020. We excluded patients with immunodeficiency disorders. Results. Among the 46 enrolled patients with IBD, CeD was identified in 4, and they did not develop any relapses. We discovered that the weight at IBD diagnosis improved significantly compared to current weight ( P -value < .0001). We also discovered that the height at diagnosis of IBD improved significantly compared to the current height ( P -value < .0001). Additionally, we found no significant associations between UC and CeD ( P -value = 1), or CD and CeD ( P -value = .625). Conclusion. No significant associations were evident between the prevalence of CeD and IBD. More prospective multicenter studies are needed to clarify the prevalence of CeD in children with IBD.